Auditorìa financiera a la cuenta caja para determinar la eficacia y efectividad en los estados financieros de la empresa “lopezcorp”, cantón quevedo, año 2023 - Suárez Bardelline, Kattya Carolina (2025)
This research project aimed to carry out a financial audit at the company Lopezcorp, driven by concerns about the clarity and reliability of its accounting information, as well as potential weaknesses in internal controls that could lead to errors or fraudulent activity. The main objective was to assess the company's financial situation and verify its compliance with current accounting regulations, in order to propose improvements that strengthen the management of the accounting and finance department. A mixed-methods approach was used, with a descriptive and field-based methodology that applied inductive, deductive, and analytical methods. Techniques such as direct observation, interviews, document review, and sampling were employed. The findings showed that approximately 35% of accounting processes presented minor inconsistencies, while 12% were linked to significant risks related to internal control. The results led to the conclusion that, although the company generally complies with legal and accounting standards, it is necessary to reinforce some internal procedures and improve documentation practices to ensure a more solid, reliable, and efficient financial management.